Neurosonogram in high-risk neonates delivered in a rural tertiary care hospital - Srinivasan, Samyukta; Kher, Anjali; Zende, Uday; Lingayat, Nitin (International Journal of Contemporary Pediatrics, 2025)
Background: A neurosonogram can detect both congenital and acquired brain lesions in neonates. Abnormal neurosonogram findings in high-risk neonates range from 3% to 47%. The aim was to study the neurosonogram findings in high-risk neonates and to associate them with maternal and neonatal risk factors. Methods: Seventy-nine high-risk neonates delivered in this rural tertiary care hospital were included. Maternal demographic data along with neonatal examination findings at birth, neurosonogram, investigations, treatment given and short-term follow-up till discharge were entered in a pre-validated proforma. In cases with abnormal neurosonogram findings, a repeat neurosonogram was done between the 8th to 28th day of life, and the findings were recorded. Statistical analysis used: The Fischer exact test was used for parameters on a categorical scale. A p≤0.05 was considered statistically significant. Results: The overall prevalence of abnormal neurosonogram findings was 11.4% with cysts, midline shifts, intraventricular haemorrhage, germinal matrix haemorrhage and hydrocephalus being the most common intracranial abnormalities detected. Factors associated with abnormal neurosonogram in high risk neonates were premature rupture of membranes, polyhydramnios, APGAR score less than seven at five and ten minutes, positive blood culture, low platelet count, low hematocrit, hypocalcaemia, low pH and high pCO2. These high risk neonates with abnormal neurosonogram had a longer hospital stay of more than 10 days and a mortality of 11.1%. Conclusions: Neurosonography is an effective screening modality for early detection of intracranial abnormalities in high-risk neonates. Morbidity and mortality were more in high risk neonates with abnormal neurosonogram.